Structural-Parametric Model of a Piezoactuator for Nanoscience and Nanotechnology - Afonin, S. M. (European Journal of Applied Sciences, 2021)
The decision of wave equation, the structural-parametric model, the structural diagram, the transfer functions of a piezoactuator for nanoscience and nanotechnology are determined. Effects of geometric and physical parameters of a piezoactuator and the external load on its dynamic characteristics are determined. The structural diagram and the transfer functions of a piezoactuator for the transverse, longitudinal, shift piezoelectric effects are obtained from the structural-parametric model of a piezoactuator in contrast to Cady’s and Mason’s electrical equivalent circuits of a piezotransducer. For calculation of the mechatronics systems for nanoscience and nanotechnology with a piezoactuator its the structural diagram and the transfer functions are obtained. The generalized structural diagram of a piezoactuator is constructed.